The Economics of Attention - George Loewenstein; Zachary Wojtowicz (Center for Economic Studies and ifo Institute (CESifo), 2023)
Attention is a pivotal resource in the modern economy and plays an increasingly prominent role in economic analysis. We summarize research on attention from both psychology and economics, placing a particular emphasis on its capacity to explain numerous documented violations of classical economic theory. We also propose promising new directions for future research, including attention-based utility, the recent proliferation of attentional externalities introduced by digital technology, the potential for artificial intelligence to compete with human attention, and the significant role that boredom, curiosity, and other motivational states play in determining how people allocate attention.
Keywords: D83; D90; D91; I00; 330; attention; motivation; behavioural bias; information; learning; education; artificial intelligence; machine learning; future of work